Real-time Data Integration in Hybrid Cloud Environments: Challenges and Solutions - Vijaya Bhaskara reddy Soperla, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the challenges and solutions in implementing real-time data integration within hybrid cloud environments. The article explores various aspects of hybrid cloud architectures, focusing on data synchronization patterns, performance optimization strategies, and security considerations. The article examines event-driven architectures, stream processing systems, and message queue implementations while addressing the complexities of maintaining data consistency across distributed environments. Through analysis of multiple implementation strategies, the article provides insights into best practices for organizations adopting hybrid cloud solutions, including architectural design principles, security frameworks, and optimization techniques. The article demonstrates the effectiveness of modern integration approaches in addressing the increasing demands for real-time data processing while maintaining security and compliance requirements.
Keywords: Cloud Computing Integration; Data Synchronization; Hybrid Architecture; Performance Optimization; Real-time Processing